Angular behaviour of critical current density in YBa2Cu3Oy thin films with crossed columnar defects. (12th May 2016) - Sueyoshi, T; Sogo, T; Nishimura, T; Fujiyoshi, T; Mitsugi, F; Ikegami, T; Awaji, S; Watanabe, K; Ichinose, A; Ishikawa, N
Abstract: Columnar defects (CDs) were installed into YBa2 Cu3 O y thin films at the crossing angle ± θ i relative to the c -axis using 200 MeV Xe ions, in order to clarify the influence of ± θ i on the angular behaviours of critical current density J c . The width of a J c peak occuring at B || c linearly increases with broadening CD-crossing angle, where its shape maintains a single peak in the range of θ i ≤ ±25°. The CDs crossing at ±45°, on the other hand, drastically change the angular behaviour of J c around B || c : the J c is equally elevated over the angular region from −45° to 45° in the lower magnetic field, whereas the rapid reduction of the J c occurs at B || c with increasing magnetic field, leading to the appearance of double peaks near the irradiation angles, ±45°. This crossover phenomenon is attributed to the difference in the pinned states of flux lines between B || c and at the irradiation angles: the CDs crossing at ±45° cannot provide the correlated flux pinning along the c -axis, resulting in the uncorrelated pinned state at B || c .